Sociology at the London School of Economics and Political Science, 1904-2015 Sound and Fury - Husbands, Christopher T. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book provides an original overall account of the history of sociology at the London School of Economics and Political Science, where the first sociology course as part of a conventional university degree programme in the UK was taught. Thus, the book is unique in its contribution to an important part of the history and development of sociology in the UK. The chapters discuss the names that - at least until the post-war period - are identified as central to the early phase of British sociology. Husbands documents the impact and influence of these leading figures through material in numerous previously little-used archives. Also explored are the culture of LSE Sociology students, their attitudes, political orientations, and academic attainments. The reputation and influence of LSE Sociology on the general development of the subject in the UK are also assessed. The book will be of interest to sociology students and scholars wanting to know about the discipline's history, as well asto those with a broader interest in higher-education policy. .